Neonatal mortality burden and trends in UNHCR refugee camps, 2006-2017: a retrospective analysis - Hannah Tappis; Marwa Ramadan; Josep Vargas; Vincent Kahi; Heiko Hering; Catrin Schulte-Hillen; Paul Spiegel (BMC, 2021)
Abstract Background More than 100 million people were forcibly displaced over the last decade, including millions of refugees displaced across international borders. Although refugee health and well-being has gained increasing attention from researchers in recent years, few studies have examined refugee birth outcomes or newborn health on a regional or global scale. This study uses routine health information system data to examine neonatal mortality burden and trends in refugee camps between 2006 and 2017. Methods Refugee population and mortality data were exported from the United Nations High Commissioner for Refugees (UNHCR) Health Information System (HIS) database. Tableau was used to export the data. Stata was used for data cleaning and statistical analysis. Neonatal mortality burdens and trends in refugee camps were analyzed and compared to national and subnational neonatal mortality rates captured by household surveys. Findings One hundred fifty refugee camps in 21 countries were included in this study, with an average population of 1,725,433 between 2006 and 2017. A total of 663,892 live births and 3382 neonatal deaths were captured during this period. Annual country-level refugee camp neonatal mortality rates (NMR) ranged from 12 to 56 neonatal deaths per 1000 live births. In most countries and years where national population-based surveys are available, refugee camp NMR as reported in the UNHCR HIS was lower than that of the immediate host community. Conclusion The UNHCR HIS provides insights into the neonatal mortality burden among refugees in camp settings and issues to consider in design and use of routine health information systems to monitor neonatal health in sub-national populations. Increased visibility of neonatal deaths and stillbirths among displaced populations can drive advocacy and inform decisions needed to strengthen health systems. Efforts to count every stillbirth and neonatal death are critical, as well as improvements to reporting systems and mechanisms for data review within broader efforts to improve the quality of neonatal care practices within and outside of health facilities.